2012
DOI: 10.1073/pnas.1117885109
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 proteoliposomes enhance fibroblast growth factor-2 (FGF-2)–induced proliferation, migration, and neovascularization of ischemic muscle

Abstract: Ischemia of the myocardium and lower limbs is a common consequence of arterial disease and a major source of morbidity and mortality in modernized countries. Inducing neovascularization for the treatment of ischemia is an appealing therapeutic strategy for patients for whom traditional treatment modalities cannot be performed or are ineffective. In the past, the stimulation of blood vessel growth was pursued using direct delivery of growth factors, angiogenic gene therapy, or cellular therapy. Although therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 30 publications
4
60
0
Order By: Relevance
“…This hypothesis is consistent with our previous finding that free syndecan-4 is not as effective in enhancing FGF-2 uptake, signaling and angiogenesis. [16] It would also be consistent with our finding of increased recycling of FGF-2 through the slow (Rab11) and fast (Rab4) mechanisms that we observed in our studies. This increased recycling may be the result of FGF-2 bound syndecan-4 being trafficked back to the surface after being internalized through the syndesome construct.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This hypothesis is consistent with our previous finding that free syndecan-4 is not as effective in enhancing FGF-2 uptake, signaling and angiogenesis. [16] It would also be consistent with our finding of increased recycling of FGF-2 through the slow (Rab11) and fast (Rab4) mechanisms that we observed in our studies. This increased recycling may be the result of FGF-2 bound syndecan-4 being trafficked back to the surface after being internalized through the syndesome construct.…”
Section: Discussionsupporting
confidence: 92%
“…[33] Our previous work has shown that delivery of syndecan-4 in a proteoliposome was more potent in inducing cell proliferation/migration, activation of ERK1/2 signaling pathway, in vitro endothelial tube formation, nuclear trafficking of growth factors and angiogenesis in comparison to the free syndecan-4 protein. [16] In our studies showed increased migration in keratinocytes and decreased invasion activity when the cells were treated with exogenous syndecan-4 protein in a proteoliposome. This would suggest that the developed treatments would be able to synergistically enhance cell therapies, including those delivered from electrospun materials.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The artery was ligated with two 6-0 silk sutures as described in our previous study. [14] Alginate beads were then applied directly to the region surrounding the femoral artery and the incision site was closed using surgical staples. The feet of the mice were imaged at 1, 3, 5, 7 and 14 days using laser speckle contrast imaging as described below.…”
Section: Methodsmentioning
confidence: 99%
“…One method to overcome this resistance is to deliver co-receptors in a proteoliposome along with the growth factors. This was tested in a diabetic mouse model and showed improved diabetic wound healing (Das et al, 2016a,c) and enhanced ischemic revascularization (Jang et al, 2012; Das et al, 2014, 2016b; Monteforte et al, 2016)(Figure 5). There are various other lipid NPs, which have shown promise for treating peripheral vascular disease and critical limb ischemia, reviewed elsewhere (Tu et al, 2015).…”
Section: Nanoparticle-based Wound Therapiesmentioning
confidence: 99%